A signal to condense - Ruggieri, Alessia; Stoecklin, Georg (Nature chemical biology, 2019)
Phase separation underlies the formation of cellular membrane-less organelles. A new report identifies deacetylation at lysine residues of intrinsically disordered protein regions to drive liquid droplet formation in vitro and stress granule maturation inside cells.
Published online: 10 December 2018
Gesehen am 23.07.2019